Development of Virtual Laboratory Media Based on Construct Application on Acid-Base Material - Firdiawan Ekaputra (EduLine: Journal of Education and Learning Innovation, 2023)
The purpose of this study was to examine the quality of virtual laboratory media utilized for developing applications on acid-base materials. This is a development study that employs the 4 D approach, which consists of the steps of define, design, develop, and disseminate. The instruments used to assess the quality of the virtual laboratory media developed were open and closed questionnaires using a Likert scale. Virtual laboratory media products that have been developed are assessed by media experts, material experts, and field trials on a limited and small scale. The limited and small scale trial samples were Jambi University Chemistry Education Study Program students consisting of 5 students in the limited scale test and 15 students in the small scale trial. The results of this study consist of qualitative and quantitative data. Qualitative data in the form of input and suggestions from media experts, material experts, and field trials who have stated that the virtual laboratory media developed has been declared suitable for use. Quantitative data is converted into a level of quality of virtual laboratory media based on assessments from limited and small-scale field tests. The results of the quantitative assessment on a small scale obtained an average of 87.26%, while on a limited scale obtained an average of 91.84%.